A Study On Working Women’s Buying Behaviour During The Covid 19 Times With Reference To Thrissur District - S, Reshma (International Journal of Psychosocial Rehabilitation, 2019)
Here the researcher is trying to find out the Buying behaviour of the working women before and during this pandemic, though the researcher belongs to the same category. There is plenty of changes in the buying styles of working women as says the women are the manager of the family. They know how to differentiate between the needs and wants in the family. The main objective of the paper is to study the changing buying behaviour of working women fraternity, especially throughout this pandemic situation. This study focuses on the Working women’s buying behaviour styles during the Covid 19.